Endoscopic papillotomy and removal of gall stones. Issue 5993 (15th November 1975) - Classen, M; Safrany, L
Abstract : Endoscopic papillotomy was attempted in 59 patients with extrahepatic obstruction of the biliary duct system and was actually performed in 50 patients. A special high-frequency diathermy knife was introduced via a duodenoscope into the terminal common bile duct and the roof of the papilla was incised. In 33 out of 39 patients with choledocholithiasis the stones passed into the duodenum spontaneously or were removed endoscopically. Papillary stenosis without ductal stones was successfully treated with this method in eight out of 11 patients. One perforation of the duodenocholedochal junction occurred and was repaired surgically. Endoscopic papillotomy and stone extraction is a relatively safe and effective method of treating extrahepatic jaundice.